EARTHQUAKE-INDUCED ROCKFALLS IN SANTOMERI VILLAGE, WESTERN GREECE - Lainas S., Lainas S.; Koulouris, S.; Vagenas, S.; Depountis, N.; Sabatakakis, N.; Koukis, G. (Bulletin of the Geological Society of Greece, 2010)
On the 8th of June 2008 an earthquake of magnitude Ms=6.5 occurred in Western Greece, affecting Achaia and Ilia Prefectures. According to state reports 2 casualties occurred, 214 people were injured and more than 15 villages and towns suffered extensive damages in properties and infrastructures. Among the secondary phenomena that were reported were extensive rockfalls that affected Santomeri village; a small village located on the western slope of the Scolis mountain. Large-sized limestone boulders, some reaching a volume up to 10m3 stroke houses and blocked roads, fortunately without casualties. The village was temporarily evacueated and the Laboratory of Engineering Geology was commissioned to undertake an Engineering Geological appraisal in order to investigate the extent of the rockfall events, assess the rockfall hazard and propose retention and protective measures so the area to be soon re-inhabited. After conducting a detailed engineering geological and geotechnical survey which included large scale engineering geological mapping, rockmass characterization and laboratory tests the inhabited area was initially divided in two zones of different rock fall risk level. By performing rockfall analyses in critical traverses a rock fall retention system, 325m long in total, comprising rock fall barrier was finally proposed.